Identifying the Burden of Digital Eye Strain: Prevalence, Clinical Manifestations, and Risk Factors in Indonesian Medical Students - Zega, Elwande Hagasaro; Selly Azmeila; Yetty Machrina; Kamal Basri Siregar (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2026)
Introduction: The increasing use of digital devices among university students, particularly in medical education, has raised concerns regarding Digital Eye Strain (DES). This study aimed to assess the prevalence, symptom profile, and risk factors of DES among Indonesian medical students. Methods: A cross-sectional study was conducted among 356 medical students using the validated Computer Vision Syndrome Questionnaire (CVS-Q). Data on demographic characteristics, ocular history, digital device usage habits, and DES symptoms were collected. Bivariate and multivariate logistic regression analyses were performed to identify factors associated with DES, with a significance level set at p < 0.05. Results: The prevalence of DES was 62.9%. Common symptoms included itchy eyes (76.8%), blurred vision (70.1%), and headaches (76.33%). Bivariate analysis revealed associations between DES and refractive errors (OR 1.889, p = 0.004), poor posture (OR 0.467, p = 0.001), and the use of more than two digital devices daily (OR 1.610, p = 0.030). Multivariate analysis identified refractive errors (OR 2.049, 95% CI: 1.300–3.227, p = 0.002), poor posture (OR 0.413, 95% CI: 0.258–0.663, p < 0.001), and the use of more than two devices (OR 1.879, 95% CI: 1.171–3.015, p = 0.009) as independent risk factors for DES. Conclusion: DES is highly prevalent among Indonesian medical students. Refractive errors, poor posture, and the concurrent use of multiple digital devices were significant risk factors. Vision screening, ergonomic education, and digital health awareness are recommended to reduce DES and support ocular health.